Public perception of COVID-19 in Saudi Arabia during the Omicron wave: recommendations for policy improvement - Almalki, Mohammed J.; Alotaibi, Amani A.; Jabour, Abdulrahman M.; Elamin, Ali; Hetany, Wafa A; Adam, Hamza Abdullah M.; Moafa, Hassan N; Alamer, Ahmed S.; Alsharif, Anwar; Almalki, Sami M. (Frontiers in Public Health, 2025)
BackgroundThe emergence of new SARS-CoV-2 variants makes it difficult to forecast potential epidemiological changes. This study investigates Saudi citizens’ perceptions of COVID-19 during the Omicron wave.MethodsWe conducted a cross-sectional study using an online survey and a convenience sample of 746 participants. The survey included questions about demographics, anxiety levels, and perception of COVID-19 during the Omicron wave.ResultsOur findings revealed that 27.3% of the participants believed that COVID-19 cases would decrease, while 30.2% believed that cases would increase; the remaining 42.5% were uncertain. When asked about the primary reasons for expecting a rise in COVID-19 cases, the two most frequently cited causes were non-adherence to prevention measures (74.7%) and the high transmissibility of the virus (66.7%). Conversely, when asked about the primary reasons for expecting a decrease in COVID-19 cases, participants cited the availability of free vaccines (60.3%), government measures (59.9%), compliance with preventive measures (57.4%), and health awareness programs (44.1%). Multivariate logistic regression analysis indicated that anxiety about COVID-19 (AOR = 1.23, 95% CI: 1.15–1.32) and education level (AOR = 1.58, 95% CI: 1.11–2.25) were significant predictors of respondents’ expectations of increases or decreases in COVID-19 cases (p < 0.05). Around 46.2% of participants were moderately to highly worried about the reinstatement of lockdowns, while 36.2% reported moderate to high levels of anxiety related to COVID-19. Ordinal logistic regression analysis showed that respondents who reported higher levels of worry about the reinstatement of lockdowns were 1.28 times more likely to experience higher levels of anxiety related to COVID-19 (p < 0.05). A few participants were hesitant to adhere to preventive measures because they had already been vaccinated or believed that COVID-19 was not real or severe. This hesitancy raises public health concerns, suggesting that some individuals may underestimate the risks associated with COVID-19 and future pandemics.ConclusionThis study provides valuable insights into how Saudi citizens perceived COVID-19 during the Omicron wave. Understanding these perceptions can guide the development of public health policies, optimize resource allocation, help control the potential transmission of viral variants, and enhance preparedness for future pandemics.